2019
DOI: 10.1039/c9ra04082j
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective carbon-supported gold-ionic liquid catalyst for acetylene hydrochlorination

Abstract: The sulfur-containing ionic liquid (IL) trimethylsulfonium iodide (C3H9SI) was used to synthesize an efficient non-mercuric catalyst with HAuCl4·4H2O as a precursor and spherical active carbon (SAC) as a support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…For the fresh catalysts (Fig. 4a and c), there appear almost no Pd dusters or nanoparticles on all USY-based supports, indicating the highly dispersed palladium particles, 52–54 which is consistent with the XRD analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…For the fresh catalysts (Fig. 4a and c), there appear almost no Pd dusters or nanoparticles on all USY-based supports, indicating the highly dispersed palladium particles, 52–54 which is consistent with the XRD analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 82%
“…This could lead to a decrease in dispersion of gold cations, reducing the activity of the catalyst. Alternatively, the lower amount of sulfur on the surface may reduce any benefit in reactant adsorption due to sulfur containing compounds, as described in the literature, [ 25 ] thereby resulting in a lower relative activity. The catalyst washed with 50 mL of H 2 O initially achieved an acetylene conversion comparable to the catalyst that underwent a wash volume of 1000 mL (58%), but this decreased at a greater rate, resulting in a catalyst which had a lower final conversion (42%, compared to 48%).…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al demonstrated the successful use of a sulfur containing ionic liquid, trimethylsulfonium iodide, in the preparation of Au/C catalysts. [25] The enhanced activity was ascribed to increased adsorption of the reactants, in particular HCl, and desorption of the VCM product. The role of sulfur moieties in carbon supported gold catalysts for this reaction has been studied in detail by Duan et al [26] The team demonstrated that high valency sulfur species such as SO 3 H and SO 2 H stabilized the cationic nature of gold nanoclusters, enabling high activity and stability, whereas low valence type molecules such as SH destabilize cationic gold leading to agglomeration and deactivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, gold catalysts have been identified as the most active and promising mercury-free catalysts, whose field has been pioneered by Hutchings's group. [4][5][6] Over the past decade, researchers have studied gold catalyst systems in detail, including singlecomponent catalysts, [7][8][9][10][11] multi-component catalysts, [12][13][14][15][16] Au-IL (ionic liquid) catalysts, 17,18 and Au-ligand catalysts. 19 According to these investigations, the introduction of other metallic or non-metallic components can increase the dispersion of gold components, stabilize the main catalytic species, and assist in improving the adsorption and activation capacity of reactants.…”
Section: Introductionmentioning
confidence: 99%